Nollywood Offering and Nigeria People and Culture: Reflections and Projection - Aondover, Perpetua Ogechi; Aondover , Eric Msughter (Universitas Islam Indonesia, 2023)
This study examined the Nollywood offering and Nigerian people and cultures, with a focus on reflections and projection. The study employed interviews and questionnaires as data collection tools. The study adopted reflective-projective theory and cultivation theory as its theoretical framework to guide the study. A sample of 400 residents of Port Harcourt City was employed using a cluster sampling technique. This study found that Nollywood films project social realities and issues in contemporary Nigerian society, and they take their coloration from Nigerian society. Most Nigerians have easy access to home movies and watch them mostly for entertainment purposes while being entertained, getting educated, or enlightened on certain things in society, such as culture, and end up being influenced in some areas of their lives. Nollywood films have a serious influence on the way audiences perceive social reality. Furthermore, the study also found that Nollywood films enable viewers to become familiar with Nigerian culture. Thus, the study concluded that Nollywood movies are avenues for the transmission of cultural heritage from generation to generation, with several appeals to their audience.